Factors influencing implementation of bylaws on sustainable crop intensification: evidence from potatoes in southwestern Uganda - Makuma-Henry, M.; Kibwika, P.; Nampala, P.; Manyong, Victor; Yami, M. (Informa UK Limited, 2020)
The study examined the factors for the successful implementation of bylaws on sustainable crop intensification. The study used the new institutionalism theory to examine the implementation of bylaws in the potato cropping system in southwestern Uganda. A mixed model featuring both qualitative and quantitative approaches was used in the study. This involved analysis of primary data. The primary sources were key informants, focus group discussions, and face to face interviews with individual farmers, as well as secondary data sources. Factors influencing the effective implementation of bylaws on sustainable crop intensification at community level included awareness of existing bylaws, availability of extension agents to sensitize and train farmers on bylaws, power relations and conflicts among farmers, and availability of financial resources for procurement of agro-inputs. The factors influencing implementation of bylaws on sustainable crop intensification at the individual level included farmers’ knowledge on bylaws (P = 0.03), farmers’ participation in activities organised by government agencies (P = 0.01), the farmers’ village/location (P = 0.03), farmers’ gender (P = 0.001), farmers’ other occupations (P = 0.01), and income earnings (P = 0.02), support of local councils and technical persons to implement bylaws (P = 0.01), and knowledge on soil and water conservation laws (P = 0.03). Thus, there is need to protect land rights (regardless of gender), create awareness on best practices and bylaws among farmers, and mobilize resources to strengthen formal and informal farmer groups to enhance sustainable crop intensification and economic development of the potato sector.